Dabrafenib plus trametinib versus nivolumab for advanced melanoma - Daniela Lahoz; Felipe Reyes; Camila Quirland (Medwave, 2023)
Introduction The incidence of cutaneous melanoma has increased worldwide over the years, and an incidence of 3 cases per 100,000 men and women is estimated in Chile. Though most of the patients are diagnosed at an early stage of the disease and have a good prognosis, advanced melanoma has poor survival results. For the treatment of melanoma, the combination of dabrafenib plus trametinib has been demonstrated to improve the outcome versus dabrafenib alone, but only indirect evidence is available for its efficacy and safety compared with immunotherapy, like nivolumab. The aim of this study is to review the available evidence to report results of efficacy and safety of dabrafenib plus trametinib in comparison with nivolumab in metastatic melanoma.